ANALISIS KEGIATAN EKSTRAKULIKULER SENI TARI DALAM MENINGKATKAN KEMAMPUAN VISIOMOTORIK SISWA KELAS 1 SD N 01 BEBENGAN - Adinesa, Azhara; Ika Ratnaningrum (Journal of Practice Learning and Educational Development, 2026)
Visiomotor ability is a crucial aspect of development for lower-grade elementary school students, as it directly affects learning readiness, particularly in activities such as writing, drawing, and movement coordination. One effort that schools can implement to stimulate this ability is through dance extracurricular activities. This study aims to analyze the implementation of dance extracurricular activities in improving the visuomotor abilities of first-grade students at SD Negeri 01 Bebengan, identify the obstacles encountered, and formulate optimization strategies. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving first-grade students, the dance extracurricular instructor, classroom teachers, and the school principal. The results indicate that dance extracurricular activities contribute positively to the improvement of students’ eye–body coordination, balance, and ability to imitate movements. The main obstacles identified include limited practice time, inadequate supporting facilities, and differences in students’ interests and abilities. Optimization strategies were carried out through adjustments in teaching methods, enhancement of supporting facilities, and collaboration between classroom teachers and extracurricular instructors. Therefore, it can be concluded that dance extracurricular activities have the potential to serve as an effective medium for improving the visiomotor abilities of lower-grade elementary school students when managed in a structured and sustainable manner.